2020
DOI: 10.1021/acs.analchem.0c03862
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of Gut Microbial Short-Chain Fatty Acids by pDART-MS

Abstract: Short-chain fatty acids (SCFAs) are small molecules ubiquitous in nature. In mammalian guts, SCFAs are mostly produced by anaerobic intestinal microbiota through the fermentation of dietary fiber. Levels of microbe-derived SCFAs are closely relevant to human health status and indicative to gut microbiota dysbiosis. However, the quantification of SCFA using conventional chromatographic approaches is often time consuming, thus limiting high-throughput screening tests. Herein, we established a novel method to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The neonatal period is a crucial window phase in developing microbial colonies, which have profound influences on piglet health. During this period, the gut microbiota and the produced SCFAs undergo wide dynamic change. Figure shows that the most abundant SCFAs in the cecum digesta was acetic acid, followed by propanoic acid and butyric acid, which demonstrated a trend consistent with previous studies . Since DMAQ derivatization significantly improved SCFA separation, 2-methylbutyric acid and 3-methylbutyric acid could be separately quantitated in cecum digesta and plasma (Figures B and A).…”
Section: Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The neonatal period is a crucial window phase in developing microbial colonies, which have profound influences on piglet health. During this period, the gut microbiota and the produced SCFAs undergo wide dynamic change. Figure shows that the most abundant SCFAs in the cecum digesta was acetic acid, followed by propanoic acid and butyric acid, which demonstrated a trend consistent with previous studies . Since DMAQ derivatization significantly improved SCFA separation, 2-methylbutyric acid and 3-methylbutyric acid could be separately quantitated in cecum digesta and plasma (Figures B and A).…”
Section: Results and Discussionsupporting
confidence: 84%
“…24−27 Figure 4 shows that the most abundant SCFAs in the cecum digesta was acetic acid, followed by propanoic acid and butyric acid, which demonstrated a trend consistent with previous studies. 28 Since DMAQ derivatization significantly improved SCFA separation, 2-methylbutyric acid and 3-methylbutyric acid could be separately quantitated in cecum digesta and plasma (Figures 4B and 5A). Comparing the changes in SCFAs during the neonatal period, it was found that there was an increase in the concentrations of most SCFAs and total SCFAs ranging from day 0 to 7 after birth and peaked on day 14.…”
Section: Selection Of Ion Pairs and Collision Energymentioning
confidence: 99%
“…The analytical sample was prepared according to the method previously described (Weng et al, 2020). 25 mg of brain and spinal cord tissue was extracted with 500uL 70% MeOH and vortexed with beads (1.0 mm dia.…”
Section: Scfa Extraction and Measurement Of Mice Brain And Spinal Cordmentioning
confidence: 99%
“…The sample was reconstituted with 25 μL MeOH. For mass analysis, each brain and spinal cord sample (2 μL) was injected into a vanquish ultra-high-performance liquid chromatography (UHPLC) system coupled with Thermo Orbitrap Elite TM (Weng et al, 2020).…”
Section: Scfa Extraction and Measurement Of Mice Brain And Spinal Cordmentioning
confidence: 99%
“…The flow rate was 0.35 mL/min with a linear gradient elution over 15 min. Reagent 1: Pyridine (Sigma-Aldrich) was adjusted with methanol to 3% (V/V) ( Weng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%